Exploring the role of environmental pollution and trade openness in human health in the context of sustainable development - Zhenzhi Lu; Lin Jiang; Xinyue Wang (PLoS ONE, 2025)
Carbon-neutral development can significantly reduce the concentration of pollutants in the atmosphere and the occurrence of human health problems through the use of clean energy and promotion of energy efficiency. Both environmental pollution and trade openness are important factors that affect human health, and this paper verifies the relationship between the three by using systematic GMM modeling. The following conclusions are drawn: (1) At the national level, although trade openness inhibits human health, this effect is not significant. From the perspective of different regions, trade openness can enhance public health in the eastern region but is unfavorable to human health in the central and western regions. (2) Environmental pollution reduces the human health level in all regions; however, it is not significant in the eastern region, which is related to the high proportion of clean energy, and the central and western regions are mainly dominated by and overly dependent on the energy industry, thus causing serious negative impacts on the environment, which is not conducive to human health. (3) Urbanization and human health show a significant and homogeneous relationship in the national and eastern samples, fail the test of significance in the central region, and have a lower level of significance in the western region. Increases in public health expenditures reduce population mortality, and the effect is significant in all regions. Increasing population size has a significant dampening effect on human health at the national level and in the western and central regions, but there is a positive ameliorating effect in the eastern region. Environmental regulatory policies can be effective in reducing population mortality in all regions, thus enhancing human health.